2009
DOI: 10.1139/x09-051
|View full text |Cite
|
Sign up to set email alerts
|

Light availability and soil source influence ectomycorrhizal fungal communities on oak seedlings grown in oak- and hemlock-associated soilsContribution No. 225 of the Louis Calder Center and Biological Station, Fordham University, Armonk, New York.

Abstract: Forests exhibit spatial heterogeneity in plant composition and light, which may influence ectomycorrhizal fungal (ECM) communities. We investigated whether light and soil source affect ECM colonization and community properties on red oak ( Quercus rubra L.) seedlings. Seedlings were grown under 10%, 45%, and full sunlight in soils removed beneath red oak and eastern hemlock ( Tsuga canadensis (L.) Carr.) trees. Between soils, colonization and diversity were significantly greater in intermediate–high versus low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This was attributed to low irradiance and its effect on seedling carbohydrate status. Other studies examining shade intolerant deciduous species have found similar trends across light gradients in oak-hemlock and beech forests (Zeleznik et al, 2007;Turner et al, 2009). Mycorrhizal networks have been shown to play an important role in facilitating carbon transfer from overstory trees to understory seedlings experiencing light limitation (Beiler et al, 2009;Courty et al, 2010).…”
Section: Em Fungi and Forest Successionmentioning
confidence: 84%
“…This was attributed to low irradiance and its effect on seedling carbohydrate status. Other studies examining shade intolerant deciduous species have found similar trends across light gradients in oak-hemlock and beech forests (Zeleznik et al, 2007;Turner et al, 2009). Mycorrhizal networks have been shown to play an important role in facilitating carbon transfer from overstory trees to understory seedlings experiencing light limitation (Beiler et al, 2009;Courty et al, 2010).…”
Section: Em Fungi and Forest Successionmentioning
confidence: 84%
“…Networks of mycorrhizae connecting individual trees and those of resource sharing via a source/sink relationship have been observed in a natural forest setting (Simard et al 1997). In the Black Rock Forest, Quercus associates with ectomycorrhizal fungi (Turner et al 2009), whereas the most common nonoak populations that dominate our field site (Acer rubrum L., A. saccharum Marsh., Nyssa sylvatica Marsh.) are commonly associated with endomycorrhizal species (Keeley 1980;Phillips and Fahey 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Only generalist fungi would be shared between angiosperms and gymnosperms (Molina et al 1992). Turner et al (2009) found that oak seedlings had lower ectomycorrhizal colonization and diversity when planted in soil from hemlock stands which provides evidence that limited fungi may be shared between oak and hemlock. Although this reduction in inoculum was evident in the growth chambers, inoculum was not limiting for the seedlings in the forest communities which implies that there may be few resistant spores in the hardwood soil but abundant hyphal inoculum.…”
Section: Growth and Root Tip Colonization In Forest Soil Treatmentsmentioning
confidence: 85%